Evaluating the efficacy of fertilisers derived from human excreta in agriculture and their perception in Antananarivo, Madagascar - Moya Diaz-Aguado, Berta; Parker, Alison; Sakrabani, Ruben; Mesa, B. (Springer, 2017)
Sustainable food production to achieve food security and increased access to safely managed sanitation are major global challenges. Treating human excreta and producing safe nutrient-rich soil amendments is an effective way of creating an incentive to tackle these two challenges. This research analysed the quality of fertilisers produced from human excreta and evaluated their acceptability within the local market. Antananarivo (Madagascar) was the field site for crop trial and three different fertilisers derived from human excreta were used to grow maize: digestate, compost and vermicompost, each derived from the previous one. The three fertilisers had different characteristics: nutrients were more concentrated in compost (23 g/kg) and vermicompost (11 g/kg) and mineralisation stages varied between them but did not cause any detrimental effect to crop yield. When compared to chemical fertilisers, the three human excreta derived fertilisers resulted in comparable yield which is encouraging. A series of 81 interviews were also carried out with farmers of the peri-urban area of Antananarivo, which highlighted the importance of characterising the market, identifying users’ perceived needs and developing a product responding to these. The majority of local farmers perceived human excreta derived fertilisers as acceptable and gave great importance to their texture and general appearance. In this study, both the field trials and interviews suggest that there is a good potential to produce fertilisers from human excreta, which have a positive effect on crops and can be adopted in the local market.
Keywords: Human excreta; Fertilisers; Compost; Vermicompost; Digestate; Crops